Cocoa Plant (Theobroma cacao) Management by Farmers in Makububui Village, East Taniwel Subdistrict, Seram Bagian Barat Regency - Elake, Welminci; Riry, Johan; Riry, Roberth Berthy (Universitas Pattimura, 2024)
Cocoa was introduced to Indonesia in 1560, first in Sulawesi, Minasa. Early exports from Manado to Manila in 1825-1838 reached 92 tons, but pest attacks damaged it. By 1928, Ambon had 10,000-12,000 cocoa trees producing 11.6 tons. Maluku, with 1,398,672 hectares of land, offers significant investment potential in the cocoa sector. In Makububui Village, cocoa is the backbone of the economy, but farmers face challenges like pests, climate change, and price fluctuations. Research in Makububui is crucial to improve cocoa productivity and support farmers with more effective policies. The goal is to understand cocoa plant management by local farmers. Descriptive research on cocoa plant management in Makububui Village, West Seram, involves 12 farmers for a month. It focuses on cocoa cultivation practices, including seed preparation, planting, maintenance, and harvesting. Data collection methods include observation, questionnaires, interviews, and documentation. Data analysis uses a descriptive approach with presentation in frequency distribution tables. Traditional cocoa management practices include watering, fertilization, pruning, and grafting. However, there is room for improvement, especially in marketing and pest control. Integration of modern technology and broader market access are needed to increase productivity. This research provides insights into cocoa management in rural areas, with recommendations for training and collaboration between government and institutions